Composite magnetic material and its preparation method and application

By using composite magnetic materials with magnetic skeletons and multi-layer composite magnetic powder in electronic equipment, the problem of poor compatibility of traditional magnetic materials in high-frequency and low-frequency environments is solved, and high magnetic permeability and electromagnetic in the 1kHz-1GHz frequency band are achieved Performance adjustment to protect electronic equipment from electromagnetic interference.

CN118866492BActive Publication Date: 2024-12-31ZHEJIANG DAHUA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411346789.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Traditional magnetic materials have high magnetic permeability in specific frequency bands, but cannot be compatible with high-frequency and low-frequency environments, resulting in degraded performance of electronic equipment and electromagnetic interference problems.

Method used

Design a composite magnetic material, including magnetic frame and composite magnetic powder. The magnetic field strength of the magnetic frame gradually increases from the center to the edge. The composite magnetic powder is divided into multiple levels according to the level, and the magnetic permeability and particle size gradually increase or decrease according to the level. Small, filled in a magnetic skeleton to achieve dynamic adjustment of high magnetic permeability and electromagnetic performance in the 1kHz-1GHz frequency band.

Benefits of technology

It realizes compatible use in high-frequency and low-frequency environments, reduces electromagnetic interference and energy loss, protects electronic devices from external interference, and adjusts electromagnetic performance according to requirements for specific scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118866492B_ABST
    Figure CN118866492B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite magnetic material and a preparation method and application thereof, wherein the composite magnetic material comprises a magnetic skeleton, the magnetic field strength of the magnetic skeleton gradually increases from the center to the edge, and the magnetic field strength at the edge differs from that at the center by more than 100 gauss; the composite magnetic powder filled in the magnetic skeleton is divided into at least three levels in the direction from the center to the edge of the magnetic skeleton, wherein the difference in magnetic permeability between the innermost composite magnetic powder and the outermost composite magnetic powder is greater than 500, the magnetic permeability of the composite magnetic powder gradually increases or decreases according to the level, and the particle size of the composite magnetic powder gradually increases according to the level. The composite magnetic material of the present invention has high magnetic permeability in the 1kHz-1GHz frequency band, and the electromagnetic performance parameters are widely dynamically adjustable, thereby achieving compatible use in high-frequency and low-frequency environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a composite magnetic material and a preparation method and application thereof. Background Art

[0002] With the rise of new energy fields such as photovoltaics, charging piles, and automotive electronics, high-voltage, high-frequency, and high-current high-power devices are becoming more and more widely used. The strong magnetic field or electromagnetic radiation generated by these high-power devices will seriously interfere with the normal operation of surrounding electronic equipment, resulting in reduced performance of electronic equipment, abnormal data transmission, and even equipment failure. At present, devices made of magnetic materials are generally used to absorb and shield corresponding electromagnetic waves. However, traditional magnetic materials only have high magnetic permeability in a specific frequency band, which limits their application areas and makes it impossible to achieve compatible use in high-frequency and low-frequency environments. Summary of the invention

[0003] Based on this, it is necessary to provide a composite magnetic material and its preparation method and application to address the above-mentioned technical problems; the composite magnetic material has high magnetic permeability in the 1kHz-1GHz frequency band, and the electromagnetic performance parameters are widely dynamically adjustable, achieving compatible use in high-frequency and low-frequency environments.

[0004] The invention discloses a composite magnetic material, comprising:

[0005] A magnetic skeleton, wherein the magnetic field strength of the magnetic skeleton gradually increases from the center to the edge, and the magnetic field strength at the edge differs from the magnetic field strength at the center by more than 100 gauss;

[0006] The composite magnetic powder filled in the magnetic skeleton is divided into at least three layers in the direction from the center to the edge of the magnetic skeleton, wherein the difference in magnetic permeability between the innermost layer of the composite magnetic powder and the outermost layer of the composite magnetic powder is greater than 500, the magnetic permeability of the composite magnetic powder gradually increases or decreases according to the layers, and the particle size of the composite magnetic powder gradually increases according to the layers.

[0007] In one embodiment, when the magnetic permeability of the composite magnetic powder gradually increases in layers, the magnetic permeability of the innermost layer of the composite magnetic powder is 500-1500, and the magnetic permeability of the outermost layer of the composite magnetic powder is 2500-3500;

[0008] When the magnetic permeability of the composite magnetic powder gradually decreases in layers, the magnetic permeability of the innermost layer of the composite magnetic powder is 2500-3500, and the magnetic permeability of the outermost layer of the composite magnetic powder is 500-1500.

[0009] In one embodiment, the particle size of the innermost layer of the composite magnetic powder is 500nm-700nm, and the particle size of the outermost layer of the composite magnetic powder is 1200nm-1500nm.

[0010] In one embodiment, the composite magnetic powder is selected from at least three of zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder, and nickel-based composite magnetic powder.

[0011] In one embodiment, the composite magnetic powder satisfies at least one of the following conditions:

[0012] (1) The magnetic permeability of the zinc-based composite magnetic powder is 500-1500, and the particle size is 500nm-700nm or 1200nm-1500nm;

[0013] (2) The magnetic permeability of the iron-based composite magnetic powder is 1200-2100, and the particle size is 600nm-900nm or 1000nm-1300nm;

[0014] (3) The magnetic permeability of the magnesium-based composite magnetic powder is 1500-2400, and the particle size is 800nm-1100nm;

[0015] (4) The magnetic permeability of the manganese-based composite magnetic powder is 2100-2800, and the particle size is 1000nm-1300nm or 600nm-900nm;

[0016] (5) The magnetic permeability of the nickel-based composite magnetic powder is 2500-3500, and the particle size is 1200nm-1500nm or 500nm-700nm.

[0017] In one embodiment, in the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder in sequence;

[0018] Alternatively, the magnetic skeleton is sequentially filled with iron-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder;

[0019] Alternatively, in the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with zinc-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder in sequence;

[0020] Alternatively, in the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with zinc-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder in sequence;

[0021] Alternatively, in the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is sequentially filled with nickel-based composite magnetic powder, manganese-based composite magnetic powder, magnesium-based composite magnetic powder, iron-based composite magnetic powder and zinc-based composite magnetic powder;

[0022] Alternatively, in a direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with manganese-based composite magnetic powder, magnesium-based composite magnetic powder and iron-based composite magnetic powder in sequence.

[0023] In one embodiment, the magnetic field strength at the center of the magnetic skeleton is greater than or equal to 30 Gauss, and the magnetic field strength at the edge of the magnetic skeleton is less than or equal to 200 Gauss;

[0024] And / or, the pore size of the magnetic skeleton is 4 to 5 times the maximum particle size of the composite magnetic powder.

[0025] In one embodiment, the magnetic framework is selected from a magnetic iron oxide framework.

[0026] In one embodiment, the mass ratio of the magnetic skeleton to the composite magnetic powder is 2:1-5:1, and the mass ratio between any two levels of composite magnetic powder is 1:2-2:1.

[0027] Different composite magnetic powders have different magnetic line loops. In the composite magnetic material provided by the present invention, the composite magnetic powder is filled into the magnetic skeleton in a specific order of particle size and magnetic permeability, so that the composite magnetic material has high magnetic permeability in the 1kHz-1GHz frequency band, and thus the current flow direction can be carried out according to the lowest impedance loop. Therefore, when the composite magnetic material is used in electronic equipment for electromagnetic wave absorption and shielding, the composite magnetic material can well reduce energy loss and electromagnetic interference in both high-frequency and low-frequency environments, thereby achieving the compatible use of composite magnetic materials in high-frequency and low-frequency environments, and thus achieving the compatible use of electronic equipment in high-frequency and low-frequency environments, protecting electronic equipment from external electromagnetic interference; in addition, by changing the type and arrangement order of the composite magnetic material, the key magnetic frequency band of the composite magnetic material can also be adjusted, so as to achieve wide dynamic adjustment of the electromagnetic properties of the composite magnetic material, so as to be applied to specific scenarios.

[0028] A method for preparing the composite magnetic material as described above comprises the following steps:

[0029] Providing at least three kinds of composite magnetic powders, wherein the particle sizes and magnetic permeabilities of the composite magnetic powders are different;

[0030] Providing a magnetic skeleton, wherein the pore size of the magnetic skeleton is larger than the maximum particle size of the composite magnetic powder;

[0031] According to the particle size level and magnetic permeability level of the composite magnetic powder, the magnetic skeleton is sequentially mixed with the composite magnetic powder, so that the composite magnetic powder is sequentially filled inside the magnetic skeleton to obtain a composite magnetic material.

[0032] In one embodiment, the method for preparing the composite magnetic powder comprises:

[0033] Under the protection of an inert gas, a metal element and a metal oxide are mixed and heated to react, and then further mixed with silicon and cooled to obtain a solidified product, wherein the metal element is selected from one of iron, zinc, nickel, manganese or magnesium, and the metal oxide includes at least one of iron oxide, manganese oxide, zinc oxide, nickel oxide or magnesium oxide;

[0034] The solidified product is crushed to obtain a crushed product, and the crushed product is classified according to particle size levels to obtain magnetic powder raw materials of different particle size levels;

[0035] The magnetic powder raw material is placed in an electromagnetic environment for magnetization to obtain composite magnetic powder.

[0036] In one embodiment, in the step of placing the magnetic powder raw material in an electromagnetic environment for magnetization,

[0037] When the metal element is selected from zinc, the magnetic field strength is 90 Gauss-110 Gauss;

[0038] When the metal element is selected from iron, the magnetic field strength is 140 Gauss-150 Gauss;

[0039] When the metal element is selected from magnesium, the magnetic field strength is 50 Gauss-65 Gauss;

[0040] When the metal element is selected from manganese, the magnetic field strength is 70 gauss to 80 gauss;

[0041] When the metal element is selected from nickel, the magnetic field strength is 120 Gauss to 130 Gauss.

[0042] In one embodiment, the method for preparing the magnetic skeleton comprises:

[0043] Under the protection of an inert gas, the iron oxide is pressurized and heated to obtain a heated product, wherein the pressure increases linearly during the pressurization step;

[0044] applying a mist coagulant to the heated product to obtain a skeleton;

[0045] The skeleton is magnetized to obtain a magnetic skeleton.

[0046] In one embodiment, in the step of magnetizing the skeleton, the magnetic field strength increases from the center to the edge of the skeleton.

[0047] In the preparation method of the composite magnetic material provided by the present invention, the magnetic skeleton is mixed with the composite magnetic powder in sequence according to the particle size level and magnetic permeability level of the composite magnetic powder, so that the composite magnetic powder is filled in the interior of the magnetic skeleton in sequence, thereby realizing the simple preparation of the composite magnetic material with high magnetic permeability in the frequency band of 1kHz-1GHz.

[0048] An application of the composite magnetic material as described above in electronic equipment.

[0049] Since the composite magnetic material of the present invention has high magnetic permeability in the frequency band of 1kHz-1GHz and the electromagnetic performance parameters are widely dynamically adjustable, when the composite magnetic material is applied to electronic devices, the electronic devices can be protected from external electromagnetic interference, thereby achieving compatible use of electronic devices in high-frequency environments and low-frequency environments. In addition, suitable composite magnetic materials can be selected according to the characteristics of different electronic devices and applied to specific scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a high-magnification scanning electron microscope image of the iron-based composite magnetic powder prepared in Example 1;

[0051] Figure 2 This is a high-magnification scanning electron microscope image of the composite magnetic material obtained in Example 1;

[0052] Figure 3 The graph is a curve showing the relationship between the magnetic permeability and frequency of the composite magnetic material prepared in Example 1. DETAILED DESCRIPTION

[0053] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0055] The present invention provides a composite magnetic material, comprising:

[0056] A magnetic skeleton, wherein the magnetic field strength of the magnetic skeleton gradually increases from the center to the edge, and the magnetic field strength at the edge differs from that at the center by more than 100 gauss;

[0057] The composite magnetic powder filled in the magnetic skeleton is divided into at least three layers from the center to the edge of the magnetic skeleton, wherein the difference in magnetic permeability between the innermost layer of composite magnetic powder and the outermost layer of composite magnetic powder is greater than 500, the magnetic permeability of the composite magnetic powder gradually increases or decreases according to the layers, and the particle size of the composite magnetic powder gradually increases according to the layers.

[0058] It should be noted that when the magnetic permeability of the composite magnetic powder in the same level differs within 200, the particle size of the composite magnetic powder in the same level differs within 150nm; in addition, the gradual increase or decrease may be a regular gradient increase or gradient decrease, or an irregular increase or decrease. Preferably, the magnetic permeability of the composite magnetic powder increases or decreases according to the level gradient, and the particle size of the composite magnetic powder increases according to the level gradient.

[0059] Different composite magnetic powders have different magnetic line loops. In the composite magnetic material provided by the present invention, the composite magnetic powders are filled into the magnetic skeleton in a specific order of particle size and magnetic permeability, so that the composite magnetic material has high magnetic permeability in the frequency band of 1kHz-1GHz, thereby enabling the current flow direction to follow the lowest impedance loop.

[0060] Therefore, when composite magnetic materials are used in electronic devices for absorbing and shielding electromagnetic waves, the composite magnetic materials can well reduce energy loss and electromagnetic interference in both high-frequency and low-frequency environments, thereby achieving the compatible use of composite magnetic materials in high-frequency and low-frequency environments, and further achieving the compatible use of electronic devices in high-frequency and low-frequency environments, protecting electronic devices from external electromagnetic interference;

[0061] In addition, by changing the type and arrangement order of the composite magnetic material, the key magnetic focusing frequency band of the composite magnetic material can be adjusted to achieve wide dynamic adjustment of the electromagnetic properties of the composite magnetic material, so that it can be applied in specific scenarios.

[0062] In one embodiment, the composite magnetic powder is selected from iron-based composite magnetic powder, zinc-based composite magnetic powder, nickel-based composite magnetic powder, manganese-based composite magnetic powder or magnesium-based composite magnetic powder.

[0063] Since the composite magnetic powders have their specific chemical composition and microstructure, the relative sizes of the magnetic permeabilities of different types of composite magnetic powders are fixed. In one embodiment, the order of the composite magnetic powders is zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder according to the magnetic permeability from small to large; preferably, the magnetic permeability of the zinc-based composite magnetic powder is 500-1500, including but not limited to 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400 or 1500; the magnetic permeability of the iron-based composite magnetic powder is 1200-2100, including but not limited to 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900 or 2000. 800, 1900, 2000 or 2100; the magnetic permeability of the magnesium-based composite magnetic powder is 1500-2400, including but not limited to 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300 or 2400; the magnetic permeability of the manganese-based composite magnetic powder is 2100-2800, including but not limited to 2100, 2200, 2300, 2400, 2500, 2600, 2700 or 2800; the magnetic permeability of the nickel-based composite magnetic powder is 2500-3500, including but not limited to 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400 or 3500.

[0064] When the magnetic permeability of the composite magnetic powder gradually increases in layers, the composite magnetic material has a high insertion loss characteristic. Therefore, when the composite magnetic material is applied to electronic equipment, the filtering function of the electronic equipment can be improved, and the composite magnetic material is suitable for power input port filtering application scenarios. Preferably, the magnetic permeability of the innermost layer of the composite magnetic powder is 500-1500, including but not limited to 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400 or 1500, and the magnetic permeability of the outermost layer of the composite magnetic powder is 2500-3500, including but not limited to 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400 or 3500; further preferably, the magnetic permeability of the innermost layer of the composite magnetic powder is 900-1100, and the magnetic permeability of the outermost layer of the composite magnetic powder is 3200-3400.

[0065] When the magnetic permeability of the composite magnetic powder gradually decreases in layers, the composite magnetic material has a high-flux magnetic characteristic. Therefore, when the composite magnetic material is applied to electronic equipment, it can improve the function of electromagnetic transmission efficiency and is suitable for power supply transformation application scenarios. Preferably, the magnetic permeability of the innermost layer of composite magnetic powder is 2500-3500, including but not limited to 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400 or 3500; the magnetic permeability of the outermost layer of composite magnetic powder is 500-1500, including but not limited to 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400 or 1500. Further preferably, the magnetic permeability of the innermost layer of composite magnetic powder is 3200-3400, and the magnetic permeability of the outermost layer of composite magnetic powder is 900-1000.

[0066] In order to better fill various composite magnetic materials in the magnetic skeleton, in one embodiment, the particle size of the composite magnetic powder closest to the center of the magnetic skeleton is 500nm-700nm, and the particle size of the composite magnetic powder farthest from the center of the magnetic skeleton is 1200nm-1500nm. It can be understood that the particle size of the composite magnetic powder is related to its position in the composite magnetic material. When the magnetic permeability of the composite magnetic powder gradually increases in level, the particle size of the zinc-based composite magnetic powder is 500nm-700nm, the particle size of the iron-based composite magnetic powder is 600nm-900nm, the particle size of the magnesium-based composite magnetic powder is 800nm-1100nm, the particle size of the manganese-based composite magnetic powder is 1000nm-1300nm, and the particle size of the nickel-based composite magnetic powder is 1000nm-1500nm. It is 1200nm-1500nm; when the magnetic permeability of the composite magnetic powder gradually decreases according to the levels, the particle size of the nickel-based composite magnetic powder is 500nm-700nm, the particle size of the manganese-based composite magnetic powder is 600nm-900nm, the particle size of the magnesium-based composite magnetic powder is 800nm-1000nm, the particle size of the iron-based composite magnetic powder is 1000nm-1300nm, and the particle size of the zinc-based composite magnetic powder is 1200nm-1500nm.

[0067] In one embodiment, the mass ratio of the magnetic skeleton to the composite magnetic powder is 2:1-5:1, including but not limited to 2:1, 3:1, 4:1 or 5:1, and the mass ratio between any two layers of composite magnetic powder is 1:2-2:1, including but not limited to 1:2, 1:1.5, 1.5:1.5, 1.5:2, 2:1.5, 1.5:1, 2:1.

[0068] In one embodiment, the magnetic framework is selected from magnetic iron oxide frameworks.

[0069] In order to make the composite magnetic powder more completely filled into the magnetic skeleton, in one embodiment, the pore size of the magnetic skeleton is 4 to 5 times the maximum particle size of the composite magnetic powder, including but not limited to 4.1 times, 4.2 times, 4.3 times, 4.4 times, 4.5 times, 4.6 times, 4.7 times, 4.8 times, 4.9 times or 5.0 times.

[0070] In order to make the composite magnetic powder more stably filled in the magnetic skeleton, in one embodiment, the magnetic field strength at the center of the magnetic skeleton is greater than or equal to 30 gauss, including but not limited to 30 gauss, 40 gauss, 50 gauss, 60 gauss, 70 gauss, 80 gauss, 90 gauss or 100 gauss, and the magnetic field strength at the edge of the magnetic skeleton is less than or equal to 200 gauss, including but not limited to 200 gauss, 190 gauss, 180 gauss, 170 gauss, 160 gauss, 150 gauss, 140 gauss or 130 gauss.

[0071] In a specific embodiment, the magnetic skeleton is filled with zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder in sequence from the center to the edge of the magnetic skeleton. At this time, the magnetic permeability of the composite magnetic material in the 1kHz-1GHz frequency band reaches more than 2100, and the insertion loss reaches more than 3dB. When the composite magnetic material is applied to electronic equipment, the electromagnetic compatibility interference suppression function can be improved, which is suitable for power supply filtering application scenarios.

[0072] In a specific embodiment, the magnetic skeleton is filled with iron-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder in sequence from the center to the edge of the magnetic skeleton. At this time, the magnetic permeability of the composite magnetic material in the 1kHz-1GHz frequency band reaches more than 2100, the key magnetic focusing frequency band is 150kHz-200MHz, and the insertion loss reaches more than 4dB. When the composite magnetic material is applied to electronic equipment, it can improve the electromagnetic compatibility interference suppression function and is suitable for power supply filtering application scenarios.

[0073] In a specific embodiment, the magnetic skeleton is filled with zinc-based composite magnetic powder, manganese-based composite magnetic powder, and nickel-based composite magnetic powder in sequence from the center to the edge of the magnetic skeleton. At this time, the magnetic permeability of the composite magnetic material in the 1kHz-1GHz frequency band reaches more than 1900, the key magnetic focusing frequency band of the composite magnetic material is 30MHz-1GHz, and the insertion loss reaches more than 3dB. When the composite magnetic material is applied to electronic equipment, the function of suppressing radiation interference can be improved, and it is suitable for application scenarios where the equipment radiation interference exceeds the standard.

[0074] In a specific embodiment, the magnetic skeleton is filled with nickel-based composite magnetic powder, manganese-based composite magnetic powder, magnesium-based composite magnetic powder, iron-based composite magnetic powder and zinc-based composite magnetic powder in sequence from the center to the edge of the magnetic skeleton. At this time, the magnetic permeability of the composite magnetic material in the 1kHz-1GHz frequency band reaches more than 2400, and the key magnetic focusing frequency band of the composite magnetic material is 30kHz-900MHz. When the composite magnetic material is applied to electronic equipment, it can improve the power supply filtering efficiency and is suitable for application scenarios of power module filtering.

[0075] In a specific embodiment, the magnetic skeleton is filled with nickel-based composite magnetic powder, manganese-based composite magnetic powder, and iron-based composite magnetic powder in sequence from the center to the edge of the magnetic skeleton. At this time, the magnetic permeability of the composite magnetic material in the 1kHz-1GHz frequency band reaches more than 1800, the key magnetic focusing frequency band of the composite magnetic material is 100kHz-2MHz, and the magnetic flux efficiency is as high as 97% or more. When the composite magnetic material is applied to electronic equipment, it can improve the power transmission efficiency and is suitable for application scenarios of power conversion circuits.

[0076] In a specific embodiment, the magnetic skeleton is filled with manganese-based composite magnetic powder, magnesium-based composite magnetic powder, and iron-based composite magnetic powder in sequence from the center to the edge of the magnetic skeleton. At this time, the magnetic permeability of the composite magnetic material in the 1kHz-1GHz frequency band reaches more than 1500, the key magnetic focusing frequency band of the composite magnetic material is 500kHz-5MHz, and the magnetic flux efficiency is as high as 95% or more. When the composite magnetic material is applied to electronic equipment, it can improve the function of high-frequency power conversion and is suitable for high-frequency power transformation application scenarios.

[0077] The present invention also provides a method for preparing the composite magnetic material as described above, comprising the following steps:

[0078] S10, providing at least three composite magnetic powders, the composite magnetic powders having different particle sizes and magnetic permeability levels;

[0079] S20, providing a magnetic skeleton, wherein the pore size of the magnetic skeleton is larger than the maximum particle size of the composite magnetic powder;

[0080] S30, mixing the magnetic skeleton with the composite magnetic powder in sequence according to the particle size level and magnetic permeability level of the composite magnetic powder, so that the composite magnetic powder is filled in the magnetic skeleton in sequence to obtain a composite magnetic material.

[0081] In the preparation method of the composite magnetic material provided by the present invention, the magnetic skeleton is mixed with the composite magnetic powder in sequence according to the particle size level and magnetic permeability level of the composite magnetic powder, so that the composite magnetic powder is filled in the interior of the magnetic skeleton in sequence, thereby realizing the simple preparation of the composite magnetic material with high magnetic permeability in the frequency band of 1kHz-1GHz.

[0082] In step S10, the composite magnetic powder is made of metal element and metal oxide as raw materials, and is mainly obtained by high temperature, crushing and magnetization. In one embodiment, the preparation method of the composite magnetic powder includes:

[0083] S101, under the protection of an inert gas, mixing a metal element with a metal oxide and heating the mixture for reaction, then further mixing the mixture with silicon and cooling the mixture to obtain a solidified product;

[0084] S102, crushing the solidified product to obtain a crushed product, and classifying the crushed product according to particle size levels to obtain magnetic powder raw materials of different particle size levels;

[0085] S103, placing the magnetic powder raw material in an electromagnetic environment for magnetization to obtain composite magnetic powder.

[0086] In step S101, the metal element is selected from one of iron, zinc, nickel, manganese or magnesium, and the metal oxide includes at least one of iron oxide, manganese oxide, zinc oxide, nickel oxide or magnesium oxide.

[0087] In one embodiment, the ratio of the mass of the metal element to the total mass of the metal oxides is 5:4.5-3:5.

[0088] In one embodiment, the metal oxide includes iron oxide, manganese oxide, zinc oxide, nickel oxide and magnesium oxide, and the mass ratio of iron oxide, manganese oxide, zinc oxide, nickel oxide and magnesium oxide is 0.5:1:1:1:1-1:1:1:1:1:1.

[0089] In the step of mixing the metal element and the metal oxide and heating them for reaction, the temperature is preferably 900° C.-1500° C., and the time is preferably 1 h-3 h.

[0090] The addition of silicon can better achieve the solidification of the heated product. Therefore, preferably, the mass ratio of the metal element to silicon is 10:1-15:1.

[0091] In step S102, during the crushing step, the rotation speed is preferably 300 r / min-500 r / min, and the pressure is preferably 150 kPa-250 kPa.

[0092] In order to make the performance of the obtained composite magnetic material more stable, after the pulverization step, the pulverized product needs to be treated to remove impurities. The specific steps include washing the pulverized product with a hydrogen peroxide solution.

[0093] In one embodiment, the pulverized product is classified according to the particle size level by the leaching method. The specific steps include: placing the pulverized product in an aqueous solution for static stratification, taking the pulverized product in the same layer, and obtaining pulverized products of the same particle size level. Preferably, the static stratification time is 1.5 hours to 2.5 hours. During the static stratification process, the pulverized product is shaken and vibrated every 15 minutes to 25 minutes to accelerate the stratification.

[0094] In step S103, in one embodiment, in the step of placing the magnetic powder raw material under an electromagnetic environment for magnetization, when the metal element is selected from zinc, the magnetic field strength is 90 gauss-110 gauss, preferably 98 gauss-102 gauss; when the metal element is selected from iron, the magnetic field strength is 140 gauss-150 gauss, preferably 143 gauss-147 gauss; when the metal element is selected from magnesium, the magnetic field strength is 50 gauss-65 gauss, preferably 58 gauss-62 gauss; when the metal element is selected from manganese, the magnetic field strength is 70 gauss-80 gauss, preferably 73 gauss-77 gauss; when the metal element is selected from nickel, the magnetic field strength is 120 gauss-130 gauss, preferably 123 gauss-127 gauss.

[0095] In step S20, the magnetic skeleton is made of iron oxide as a raw material, and is mainly obtained by heating, expansion and magnetization. In one embodiment, the step of providing the magnetic skeleton includes:

[0096] S201, under the protection of an inert gas, pressurizing and heating the iron oxide to obtain a heated product, wherein in the pressurizing step, the pressure increases linearly;

[0097] S202, applying a mist coagulant to the heated product to obtain a skeleton;

[0098] S203, magnetizing the skeleton to obtain a magnetic skeleton.

[0099] In step S201, pressurization can prevent the iron oxide from breaking during the heating process. Preferably, in the pressurization step, the pressure is increased from 3kPa-7kPa to 40kPa-70kPa, including but not limited to from 3kPa to 40kPa, from 4kPa to 45kPa, from 5kPa to 50kPa, from 6kPa to 60kPa, and from 7kPa to 70kPa; the increasing rate is 0.8kPa / 5min-1.2kPa / 5min, including but not limited to 0.8kpa / 5min, 0.9kpa / 5min, 1.0kpa / 5min, 1.1kpa / 5min or 1.2kpa / 5min.

[0100] In the heating step, the temperature is 200°C-300°C, including but not limited to 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C.

[0101] In step S202, the step of applying the atomized coagulant to the heated product includes: atomizing the gel compound and spraying it on the surface of the heated product.

[0102] In one embodiment, the atomized coagulant includes at least one of silica gel, alumina gel or ferric hydroxide gel. In order to ensure that the atomized coagulant is evenly sprayed on the skeleton and does not fill the skeleton, preferably, the mass ratio of the heated product to the atomized coagulant is 15:1-10:1, including but not limited to 15:1, 14:1, 13:1, 12:1, 11:1 or 10:1.

[0103] In step S203, in one embodiment, in the step of magnetizing the skeleton, the magnetic field strength increases from the center of the skeleton to the edge. Specifically, the magnetic field strength at the center of the skeleton is 30-50 gauss, including but not limited to 30 gauss, 32 gauss, 34 gauss, 36 gauss, 38 gauss, 40 gauss, 42 gauss, 44 gauss, 46 gauss, 48 ​​gauss or 50 gauss, and the magnetic field strength at the edge is 170-200 gauss, including but not limited to 170 gauss, 175 gauss, 180 gauss, 185 gauss, 190 gauss, 195 gauss or 200 gauss.

[0104] The present invention also provides an application of a composite magnetic material in electronic devices, such as in common-mode inductors, transformers or differential-mode inductors. Since the composite magnetic material of the present invention has high magnetic permeability in the 1kHz-1GHz frequency band and the electromagnetic performance parameters are widely dynamically adjustable, when the composite magnetic material is applied to electronic devices, the electronic devices can be protected from external electromagnetic interference, thereby achieving compatible use of electronic devices in high-frequency and low-frequency environments. In addition, suitable composite magnetic materials can be selected according to the characteristics of different electronic devices and applied to specific scenarios.

[0105] Hereinafter, the composite magnetic material and its preparation method and application will be further described through the following specific embodiments.

[0106] Example 1

[0107] Under the protection of inert gas, a metal single substance is mixed with a mixture of Fe2O3, Mn3O4, ZnO, NiO and MgO and heated, wherein the metal single substance is selected from zinc, iron, magnesium, manganese or nickel. When the metal single substance is selected from zinc, the mass ratio of zinc to Fe2O3, Mn3O4, ZnO, NiO and MgO is 4.5: 0.5: 1: 1: 1: 1, the heating temperature is 900°C, and the heating time is 1.5 hours. When the metal single substance is selected from iron, the mass ratio of iron to Fe2O3, Mn3O4, ZnO, NiO and MgO is 5: 0.5: 1: 1: 1: 1, the heating temperature is 1450°C, and the heating time is 2.5 hours. When the metal single substance is selected from magnesium, the mass ratio of magnesium to Fe2O3, Mn3O4, ZnO, NiO and MgO is 4: 0.5:1:1:1:1, the heating temperature is 1000℃, and the heating time is 1 hour. When the metal element is selected from manganese, the mass ratio of manganese to Fe2O3, Mn3O4, ZnO, NiO, and MgO is 3:1:1:1:1:1:1, the heating temperature is 1200℃, and the heating time is 3 hours. When the metal element is selected from nickel, the mass ratio of nickel to Fe2O3, Mn3O4, ZnO, NiO, and MgO is 4:1:1:1:1:1:1, the heating temperature is 1300℃, and the heating time is 2 hours. Then, silicon is added to the heated products respectively, the mass ratio of the metal element to silicon is 15:1, and the products are solidified at 20℃-40℃ to obtain solidified products.

[0108] The solidified products obtained were pulverized to obtain pulverized products, and the pulverized products were washed with a hydrogen peroxide solution with a concentration of 8.1 mol / L to remove impurities, and then washed with ammonia water with a mass fraction of 20% to remove the hydrogen peroxide solution remaining on the surface of the pulverized products. The particle size of the zinc-based pulverized product is 550nm-650nm, the particle size of the iron-based pulverized product is 650nm-850nm, the particle size of the magnesium-based pulverized product is 850nm-1050nm, the particle size of the manganese-based pulverized product is 1100nm-1300nm, and the particle size of the nickel-based pulverized product is 1300nm-1500nm. The pulverized product is layered by a leaching method and then dried to obtain a magnetic powder raw material, wherein the particle size of the zinc-based magnetic powder raw material is 600nm±50nm, the particle size of the iron-based magnetic powder raw material is 775nm±75nm, the particle size of the magnesium-based magnetic powder raw material is 950nm±50nm, the particle size of the manganese-based magnetic powder raw material is 1250nm±50nm, and the particle size of the nickel-based magnetic powder raw material is 1350nm±50nm.

[0109] The magnetic powder raw material is placed in an electromagnetic environment for magnetization to obtain composite magnetic powder. During the magnetization of the zinc-based magnetic powder raw material, the magnetic field strength is 100 Gauss, and the magnetic permeability of the zinc-based composite magnetic powder is 750. During the magnetization of the iron-based magnetic powder raw material, the magnetic field strength is 145 Gauss, and the magnetic permeability of the iron-based composite magnetic powder is 1300. The high-magnification scanning electron microscope image of the iron-based composite magnetic powder is as follows: Figure 1 As shown, during the magnetization of the magnesium-based magnetic powder raw material, the magnetic field strength is 60 Gauss, and the magnetic permeability of the magnesium-based composite magnetic powder is 1800. During the magnetization of the manganese-based magnetic powder raw material, the magnetic field strength is 75 Gauss, and the magnetic permeability of the manganese-based composite magnetic powder is 2300. During the magnetization of the nickel-based magnetic powder raw material, the magnetic field strength is 125 Gauss, and the magnetic permeability of the nickel-based composite magnetic powder is 3400.

[0110] Under the protection of inert gas, the iron oxide is pressurized and heated to obtain a heated product, wherein the pressure increases from 5 kPa to 50 kPa, the increase rate is 1 kPa / 5 min, the temperature is 250°C, and the time is 1 hour.

[0111] A mist coagulant silica gel is applied to the heated product, wherein the mass ratio of the heated product to the mist coagulant is 12:1.

[0112] The skeleton is magnetized, and the magnetic field strength increases from the center of the skeleton to the edge. Specifically, the magnetic field strength at the center of the skeleton is 40 Gauss, and the magnetic field strength at the edge is 180 Gauss, thereby obtaining an iron oxide magnetic skeleton. The magnetic field strength at the center of the iron oxide magnetic skeleton is 35 Gauss, and the magnetic field strength at the edge is 175 Gauss. The pore size of the magnetic skeleton is 6μm-8μm.

[0113] The iron oxide magnetic skeleton is sequentially mixed with zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder, and subjected to magnetic vibration. The mass ratio of the iron oxide magnetic skeleton, zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder is 15:2:1.5:1.5:1:1.5 to obtain a composite magnetic material. In the composite magnetic material, the mass ratio of the magnetic skeleton to the composite magnetic powder is 2:1. A high-power scanning electron microscope image of the composite magnetic material is shown in FIG. Figure 2 shown.

[0114] Comparative Example 1

[0115] Comparative Example 1 is carried out with reference to Example 1, except that only the iron-based composite magnetic powder is mixed with the iron oxide magnetic skeleton for mixing and magnetic vibration, and the amount of the iron-based composite magnetic powder is the total mass of the iron-based composite magnetic powder, zinc-based composite magnetic powder, nickel-based composite magnetic powder, manganese-based composite magnetic powder, and magnesium-based composite magnetic powder in Example 1.

[0116] Comparative Example 2

[0117] Comparative Example 2 was carried out with reference to Example 1, except that only the magnesium-based composite magnetic powder was mixed with the iron oxide magnetic skeleton for mixing and magnetic vibration, and the amount of the magnesium-based composite magnetic powder was the total mass of the iron-based composite magnetic powder, zinc-based composite magnetic powder, nickel-based composite magnetic powder, manganese-based composite magnetic powder, and magnesium-based composite magnetic powder in Example 1.

[0118] Comparative Example 3

[0119] Comparative Example 3 is carried out with reference to Example 1, except that the zinc-based composite magnetic powder, iron-based composite magnetic powder, manganese-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder are first mixed, and then the obtained mixture is mixed with the iron oxide magnetic skeleton and magnetically vibrated.

[0120] Comparative Example 4

[0121] Comparative Example 4 was carried out with reference to Example 1, except that the order of adding the composite magnetic powders into the iron oxide magnetic skeleton was adjusted, and the order of adding the composite magnetic powders was zinc-based composite magnetic powder, iron-based composite magnetic powder, manganese-based composite magnetic powder, magnesium-based composite magnetic powder, and nickel-based composite magnetic powder.

[0122] Comparative Example 5

[0123] Comparative Example 5 was carried out with reference to Example 1, except that the iron oxide magnetic skeleton was mixed with the iron-based composite magnetic powder and the magnesium-based composite magnetic powder in sequence and magnetically vibrated, wherein the total amount of the iron-based composite magnetic powder and the magnesium-based composite magnetic powder was the total mass of the iron-based composite magnetic powder, zinc-based composite magnetic powder, nickel-based composite magnetic powder, manganese-based composite magnetic powder, and magnesium-based composite magnetic powder in Example 1, and the mass ratio of the iron-based composite magnetic powder to the magnesium-based composite magnetic powder was 1:1.

[0124] Test Example 1

[0125] The magnetic properties of the composite magnetic materials obtained in Example 1 and Comparative Examples 1 to 5 were tested. The test method is as follows. The test results are shown in Table 1. The relationship curve between the magnetic permeability and frequency of the composite magnetic material obtained in Example 1 is as follows: Figure 3 As shown, from Figure 3 It can be seen that the composite magnetic material has high magnetic permeability in the 1kHz-1GHz frequency band. Figure 3 In the figure, μ' represents the real part of the magnetic permeability and μ" represents the imaginary part of the magnetic permeability.

[0126] Magnetic focusing performance test: refer to "JB / T 13536-2018", the key magnetic focusing frequency band with magnetic permeability above 1000, and test the magnetic permeability of composite magnetic materials in the key magnetic focusing frequency band.

[0127] Wave absorption performance test: Refer to GB / T32596 and test insertion loss.

[0128] Table 1

[0129]

[0130] Example 2

[0131] Example 2 is carried out with reference to Example 1, except that the mass ratio of the zinc-based composite magnetic powder, the iron-based composite magnetic powder, the magnesium-based composite magnetic powder, the manganese-based composite magnetic powder, and the nickel-based composite magnetic powder is 1:1:1:1:1.5.

[0132] Example 3

[0133] Example 3 is carried out with reference to Example 1, except that the mass ratio of the zinc-based composite magnetic powder, the iron-based composite magnetic powder, the magnesium-based composite magnetic powder, the manganese-based composite magnetic powder, and the nickel-based composite magnetic powder is 1:1.5:1:1:1.

[0134] Example 4

[0135] Example 4 was carried out with reference to Example 1, except that in the step of pressurizing and heating the iron oxide, the temperature was 200°C.

[0136] Example 5

[0137] Example 5 was carried out with reference to Example 1, except that in the step of pressurizing and heating the iron oxide, the temperature was 300°C.

[0138] Example 6

[0139] Example 6 is carried out with reference to Example 1, except that, during the magnetization of the zinc-based magnetic powder raw material, the magnetic field strength is 90 Gauss, and the magnetic permeability of the zinc-based composite magnetic powder is 600; during the magnetization of the iron-based magnetic powder raw material, the magnetic field strength is 140 Gauss, and the magnetic permeability of the iron-based composite magnetic powder is 1200; during the magnetization of the magnesium-based magnetic powder raw material, the magnetic field strength is 50 Gauss, and the magnetic permeability of the magnesium-based composite magnetic powder is 1500; during the magnetization of the manganese-based magnetic powder raw material, the magnetic field strength is 70 Gauss, and the magnetic permeability of the manganese-based composite magnetic powder is 2100; during the magnetization of the nickel-based magnetic powder raw material, the magnetic field strength is 120 Gauss, and the magnetic permeability of the nickel-based composite magnetic powder is 2500.

[0140] Example 7

[0141] Example 7 is carried out with reference to Example 1, except that, during the magnetization of the zinc-based magnetic powder raw material, the magnetic field strength is 110 Gauss, and the magnetic permeability of the zinc-based composite magnetic powder is 800, during the magnetization of the iron-based magnetic powder raw material, the magnetic field strength is 150 Gauss, and the magnetic permeability of the iron-based composite magnetic powder is 1300, during the magnetization of the magnesium-based magnetic powder raw material, the magnetic field strength is 65, and the magnetic permeability of the magnesium-based composite magnetic powder is 1900, during the magnetization of the manganese-based magnetic powder raw material, the magnetic field strength is 80, and the magnetic permeability of the manganese-based composite magnetic powder is 2200, and during the magnetization of the nickel-based magnetic powder raw material, the magnetic field strength is 130, and the magnetic permeability of the nickel-based composite magnetic powder is 3200.

[0142] Example 8

[0143] Example 8 is carried out with reference to Example 1, except that the particle size of the zinc-based magnetic powder raw material is 550nm±50nm, the particle size of the iron-based magnetic powder raw material is 650nm±50nm, the particle size of the magnesium-based magnetic powder raw material is 850nm±50nm, the particle size of the manganese-based magnetic powder raw material is 1050nm±50nm, and the particle size of the nickel-based magnetic powder raw material is 1250nm±50nm.

[0144] Example 9

[0145] Example 9 is carried out with reference to Example 1, except that the particle size of the zinc-based magnetic powder raw material is 650nm±50nm, the particle size of the iron-based magnetic powder raw material is 850nm±50nm, the particle size of the magnesium-based magnetic powder raw material is 1050nm±50nm, the particle size of the manganese-based magnetic powder raw material is 1250nm±50nm, and the particle size of the nickel-based magnetic powder raw material is 1450nm±50nm.

[0146] Example 10

[0147] Example 10 is carried out with reference to Example 1, except that the magnetic permeability of the composite magnetic powder gradually decreases in layers from the center to the edge of the magnetic skeleton. Specifically, the particle size of the nickel-based composite magnetic powder is 600nm±50nm, the particle size of the manganese-based composite magnetic powder is 775nm±75nm, the particle size of the magnesium-based composite magnetic powder is 950nm±50nm, the particle size of the iron-based composite magnetic powder is 1250nm±50nm, and the particle size of the zinc-based composite magnetic powder is 1350nm±50nm. At the same time, the iron oxide magnetic skeleton is sequentially mixed with the nickel-based composite magnetic powder, the manganese-based composite magnetic powder, the magnesium-based composite magnetic powder, the iron-based composite magnetic powder, and the zinc-based composite magnetic powder, and subjected to magnetic vibration to obtain a composite magnetic material.

[0148] Test Example 2

[0149] The magnetic properties of the composite magnetic materials obtained in Examples 2 to 10 were tested with reference to Test Example 1. The test results are shown in Table 2.

[0150] Table 2

[0151]

[0152] Embodiment 11

[0153] Example 11 is carried out with reference to Example 1, except that the iron oxide magnetic skeleton is sequentially mixed with iron-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder and magnetically vibrated, and in the composite magnetic material, the magnetic skeleton is sequentially filled with iron-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder in a direction from the center to the edge of the magnetic skeleton.

[0154] Example 12

[0155] Example 12 is carried out with reference to Example 1, except that the iron oxide magnetic skeleton is sequentially mixed with zinc-based composite magnetic powder, manganese-based composite magnetic powder, and nickel-based composite magnetic powder and magnetically vibrated, and the composite magnetic material is sequentially filled with zinc-based composite magnetic powder, manganese-based composite magnetic powder, and nickel-based composite magnetic powder in the direction from the center to the edge of the magnetic skeleton.

[0156] Example 13

[0157] Example 13 is carried out with reference to Example 10, except that the iron oxide magnetic skeleton is sequentially mixed with nickel-based composite magnetic powder, manganese-based composite magnetic powder, and iron-based composite magnetic powder and magnetically vibrated, and the composite magnetic material is sequentially filled with nickel-based composite magnetic powder, manganese-based composite magnetic powder, and iron-based composite magnetic powder in the direction from the center to the edge of the magnetic skeleton.

[0158] Embodiment 14

[0159] Example 14 is carried out with reference to Example 10, except that the iron oxide magnetic skeleton is sequentially mixed with manganese-based composite magnetic powder, magnesium-based composite magnetic powder, and iron-based composite magnetic powder and magnetically vibrated, and in the composite magnetic material, the magnetic skeleton is sequentially filled with manganese-based composite magnetic powder, magnesium-based composite magnetic powder, and iron-based composite magnetic powder in the direction from the center to the edge of the magnetic skeleton.

[0160] Test Example 3

[0161] The magnetic properties of the composite magnetic materials obtained in Examples 11 to 14 were tested with reference to Test Example 1. The test results are shown in Table 3.

[0162] Table 3

[0163]

[0164] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0165] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A composite magnetic material, characterized in that: include: A magnetic skeleton, wherein the magnetic field strength of the magnetic skeleton gradually increases from the center to the edge, and the magnetic field strength at the edge differs from the magnetic field strength at the center by more than 100 gauss; The composite magnetic powder filled in the magnetic skeleton is divided into at least three levels in the direction from the center to the edge of the magnetic skeleton, wherein the difference in magnetic permeability between the innermost layer of the composite magnetic powder and the outermost layer of the composite magnetic powder is greater than 500, and the magnetic permeability of the composite magnetic powder gradually increases or decreases according to the levels. When the magnetic permeability of the composite magnetic powder gradually increases according to the levels, the magnetic permeability of the innermost layer of the composite magnetic powder is 500-1500, and the magnetic permeability of the outermost layer of the composite magnetic powder is 2500-3500; when the magnetic permeability of the composite magnetic powder gradually decreases according to the levels, the magnetic permeability of the innermost layer of the composite magnetic powder is 2500-3500, and the magnetic permeability of the outermost layer of the composite magnetic powder is 500-1500; The particle size of the composite magnetic powder increases gradually in layers. The particle size of the innermost layer of the composite magnetic powder is 500nm-700nm, and the particle size of the outermost layer of the composite magnetic powder is 1200nm-1500nm.

2. The composite magnetic material according to claim 1, characterized in that: The composite magnetic powder is selected from at least three of zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder or nickel-based composite magnetic powder.

3. The composite magnetic material according to claim 2, characterized in that: The composite magnetic powder satisfies at least one of the following conditions: (1) The magnetic permeability of the zinc-based composite magnetic powder is 500-1500, and the particle size is 500nm-700nm or 1200nm-1500nm; (2) The magnetic permeability of the iron-based composite magnetic powder is 1200-2100, and the particle size is 600nm-900nm or 1000nm-1300nm; (3) The magnetic permeability of the magnesium-based composite magnetic powder is 1500-2400, and the particle size is 800nm-1100nm; (4) The magnetic permeability of the manganese-based composite magnetic powder is 2100-2800, and the particle size is 1000nm-1300nm or 600nm-900nm; (5) The magnetic permeability of the nickel-based composite magnetic powder is 2500-3500, and the particle size is 1200nm-1500nm or 500nm-700nm.

4. The composite magnetic material according to claim 2, characterized in that: In the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with zinc-based composite magnetic powder, iron-based composite magnetic powder, magnesium-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder in sequence; Alternatively, the magnetic skeleton is sequentially filled with iron-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder; Alternatively, in the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with zinc-based composite magnetic powder, manganese-based composite magnetic powder and nickel-based composite magnetic powder in sequence; Alternatively, in the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with zinc-based composite magnetic powder, magnesium-based composite magnetic powder and nickel-based composite magnetic powder in sequence; Alternatively, in the direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is sequentially filled with nickel-based composite magnetic powder, manganese-based composite magnetic powder, magnesium-based composite magnetic powder, iron-based composite magnetic powder and zinc-based composite magnetic powder; Alternatively, in a direction from the center to the edge of the magnetic skeleton, the magnetic skeleton is filled with manganese-based composite magnetic powder, magnesium-based composite magnetic powder and iron-based composite magnetic powder in sequence.

5. The composite magnetic material according to claim 1, characterized in that: The magnetic field strength at the center of the magnetic skeleton is greater than or equal to 30 Gauss, and the magnetic field strength at the edge of the magnetic skeleton is less than or equal to 200 Gauss; And / or, the pore size of the magnetic skeleton is 4 to 5 times the maximum particle size of the composite magnetic powder.

6. The composite magnetic material according to claim 1, characterized in that: The magnetic framework is selected from magnetic iron oxide frameworks.

7. The composite magnetic material according to claim 1, characterized in that: The mass ratio of the magnetic skeleton to the composite magnetic powder is 2:1-5:1, and the mass ratio between any two levels of composite magnetic powder is 1:2-2:

1.

8. A method for preparing a composite magnetic material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Providing at least three kinds of composite magnetic powders, wherein the particle sizes and magnetic permeabilities of the composite magnetic powders are different; Providing a magnetic skeleton, wherein the pore size of the magnetic skeleton is larger than the maximum particle size of the composite magnetic powder; According to the particle size level and magnetic permeability level of the composite magnetic powder, the magnetic skeleton is sequentially mixed with the composite magnetic powder, so that the composite magnetic powder is sequentially filled inside the magnetic skeleton to obtain a composite magnetic material.

9. The method for preparing a composite magnetic material according to claim 8, characterized in that: The preparation method of the composite magnetic powder comprises: Under the protection of an inert gas, a metal element and a metal oxide are mixed and heated to react, and then further mixed with silicon and cooled to obtain a solidified product, wherein the metal element is selected from one of iron, zinc, nickel, manganese or magnesium, and the metal oxide includes at least one of iron oxide, manganese oxide, zinc oxide, nickel oxide or magnesium oxide; The solidified product is crushed to obtain a crushed product, and the crushed product is classified according to particle size levels to obtain magnetic powder raw materials of different particle size levels; The magnetic powder raw material is placed in an electromagnetic environment for magnetization to obtain composite magnetic powder.

10. The method for preparing a composite magnetic material according to claim 9, characterized in that: In the step of placing the magnetic powder raw material in an electromagnetic environment for magnetization, When the metal element is selected from zinc, the magnetic field strength is 90 Gauss-110 Gauss; When the metal element is selected from iron, the magnetic field strength is 140 Gauss-150 Gauss; When the metal element is selected from magnesium, the magnetic field strength is 50 Gauss-65 Gauss; When the metal element is selected from manganese, the magnetic field strength is 70 gauss to 80 gauss; When the metal element is selected from nickel, the magnetic field strength is 120 Gauss to 130 Gauss.

11. The method for preparing a composite magnetic material according to claim 8, characterized in that: The preparation method of the magnetic skeleton comprises: Under the protection of an inert gas, the iron oxide is pressurized and heated to obtain a heated product, wherein the pressure increases linearly during the pressurization step; applying a mist coagulant to the heated product to obtain a skeleton; The skeleton is magnetized to obtain a magnetic skeleton.

12. The method for preparing a composite magnetic material according to claim 11, characterized in that: In the step of magnetizing the skeleton, the magnetic field strength increases from the center to the edge of the skeleton.

13. Use of the composite magnetic material according to any one of claims 1 to 7 in electronic equipment.